Protective immunity to Listeria Monocytogenes infection mediated by recombinant Listeria innocua harboring the vgc locus - Mohamed, Walid; Sethi, Shneh; Tchatalbachev, Svetlin; Darji, Ayub; Chakraborty, Trinad; Justus Liebig University Giessen (My University, 2012)
In this study we propose a novel bacterial vaccine strategy where non-pathogenic bacteria are complemented with traits desirable for the induction of protective immunity. To illustrate the proof of principle of this novel vaccination strategy, we use the model organism of intracellular immunity Listeria. We introduced a, low copy number BAC-plasmid harbouring the virulence gene cluster (vgc) of L. monocytogenes (Lm) into the non-pathogenic L. innocua (L.inn) strain and examined for its ability to induce protective cellular immunity. The resulting strain (L.inn::vgc) was attenuated for virulence in vivo and showed a strongly reduced host detrimental inflammatory response compared to Lm. Like Lm, L.inn::vgc induced the production of Type I Interferon´s and protection was mediated by Listeria-specific CD8+ T cells. Rational vaccine design whereby avirulent strains are equipped with the capabilities to induce protection but lack detrimental inflammatory effects offer great promise towards future studies using non-pathogenic bacteria as vectors for vaccination.
Keywords: bacterial vaccine strategy; protective cellular immunity; Listeria monocytogenes; non-pathogenic bacteria as vectors for vaccination; ddc:610